Accessibility to urban parks in Montreal from the perspective of children - Reyes, Mario; Páez, Antonio; Morency, Catherine (Congreso Chileno de Ingeniería de Transporte, 2013)
Parks are elemental components of urban environments that provide environmental value and serve valuable social functions. In order to enjoy the beneficial opportunities for activities in parks, users must have reasonable access to these resources. The objective of this paper is to measure accessibility to urban parks from the perspective of children travelling by walking in the island of Montreal, Canada. We evaluate the relationship between the distribution of children population and conditions of accessibility to urban parks, in order to understand the potential for use and possible spatial disparities in the distribution of valuable environmental resources. This research contributes to the assessment of the distribution of access to urban parks by children, and can inform planners and policy makers in order to improve the supply of public facilities (parks) from a transportation perspective.